Immiscible poly(lactic acid)/poly(ε-caprolactone) for temporary implants: Compatibility and cytotoxicity - Finotti, Pablo F.M.; Costa, Lidiane C.; Capote, Ticiana S.O. [UNESP]; Scarel-Caminaga, Raquel M. [UNESP]; Chinelatto, Marcelo A. (Elsevier, 2017)
This manuscript focuses on the effect of the addition of a low molecular weight triblock copolymer derived from ε-caprolactone and tetrahydrofuran (CT) on the compatibility and cytotoxicity of immiscible poly(lactic acid) (PLA) and poly(ε-caprolactone) (PCL) blends. Binary and tertiary PLA/PCL blends were prepared by melt mixing in a twin-screw extruder and their morphological, mechanical and thermal behaviors were investigated by scanning electron microscopy (SEM), tensile and Izod impact test, dynamic mechanical analysis (DMA) and differential scanning calorimetry (DSC). SEM micrographs showed the CT copolymer suppressed the coalescence phenomena and maintained the size of dispersed PCL domains at approximately 0.35 µm. Bioresorbable PLA/PCL blends containing 5 wt% of CT copolymer exhibited a remarkable increase in ductility and improved toughness at room temperature. Although the CT copolymer increased the interfacial adhesion, the DMA results suggest it also acts as a plasticizer exclusively for the PCL phase. The cell viability evaluated by the XTT assay confirmed PLA/PCL blends compatibilized by CT copolymer exerted no cytotoxic effect.
Keywords: Compatibility; Cytotoxicity; Mechanical properties; Morphology; PLA/PCL blends